Making Agriculture Work for the Poor in Timor-Leste - World Bank (World Bank, Washington, DC, 2019)
About 80 percent of the poor households in Timor-Leste live in rural areas and are dependent on agriculture for their livelihood. It is therefore widely acknowledged that growth in the agriculture sector is an important channel through which poverty can be reduced in the country. That notwithstanding, the country’s agricultural production system is one of the least developed in the world and all subsectors are dominated by subsistence systems and by farmers who are very risk averse. Agricultural productivity in the country is also well below that of other small island developing states and has fallen below the average for other low-income, food-deficit countries in recent years making the sector underperform in terms of its contribution to food security, sufficient livelihood, and overall economic growth. Using data from the 2007 and 2014 of the Timor-Leste Survey of Living Standards, the note provides insight into the extent to which increases in agricultural productivity can contribute to poverty reduction, including assessing the drivers of, and identifying the constraints to, increasing agricultural productivity in the country. The note finds that improvements in agricultural productivity reduce the probability of being poor among agricultural households. Yet, improving productivity goes beyond the confines of raising yield or decreasing cost to include enhancing food quality and promoting higher value products. To do so, the following factors ought to be considered: facilitation of mechanization, improvement in the use of chemical (fertilizer, pesticides, and herbicides) inputs, enhancement in access to credit and extension, encouragement to farmers to join farmer groups, expansion of the commercialization of farm produce, and reduction in the gender gap in agricultural productivity. Investment in the sector can be improved by allocating the limited public funds more strategically and better correspond with local poverty. The findings from this study contribute to existing evidence pertinent to guide how agricultural policy can effectively help reducing poverty in the country.